The murder room : the heirs of Sherlock Holmes gather to solve the world's most perplexing cold cases - Capuzzo, Michael (Gotham Books, 2010)
Documents the efforts of the Vidocq Society, an elite trio of gifted investigators, to solve such notorious cold cases as those of JonBenet Ramsey, the Butcher of Cleveland, and Jack the Ripper, and details their work with the world's top forensic specialists.